2008
DOI: 10.1093/cesifo/ifn030
|View full text |Cite
|
Sign up to set email alerts
|

What Explains Germany's Rebounding Export Market Share?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 6 publications
0
29
0
1
Order By: Relevance
“…On the contrary, Germany was able to recover from a significantly downward trend in its market share by increasing its competitiveness. At the root of this performance, there are increased investment in R&D, structural reforms and changes in the production system of large exporters, which allowed Germany to expand its exports in new destinations and sectors (Danninger and Joutz, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Germany was able to recover from a significantly downward trend in its market share by increasing its competitiveness. At the root of this performance, there are increased investment in R&D, structural reforms and changes in the production system of large exporters, which allowed Germany to expand its exports in new destinations and sectors (Danninger and Joutz, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The recent literature on the price-elasticity of German exports (whose results are summarized in Appendix A) has the following common features: (a) the basic specification is growth of export volumes regressed on foreign demand and relative price differences; (b) the model is estimated in first differences if no evidence of cointegration is found or with some variant of the error correction model (ECM) otherwise; (c) results tend to vary considerably depending on the indicator of price competitiveness used (Bayoumi et al, 2011) and the time period selected. With regard to the post-unification period, studies whose coverage ends in the early 2000s tend to find smaller or even insignificant elasticities (Stahn, 2006;Danninger and Joutz, 2008), while studies reaching the early 2010s find greater elasticities suggesting the possibility of growing effects over time (Thorbecke and Kato, 2012;Breuer and Klose, 2014;European Commission, 2014).…”
Section: The Price-elasticity Of German Exportsmentioning
confidence: 99%
“…The industry elasticities have increased over time, especially in industries subject to increasing product market competition. Danninger and Joutz (2008) tried to compute Germany's export market shares (EMS) and investigate its determinants. The empirical results indicated that the dominant factors explaining the increase in market share are trade relationships with fast growing countries and regionalized production in the export sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The EMS can be calculated as the following equation: (Carlin et al, 2001;Danninger and Joutz, 2008). It should be noted that EMS doesn"t take the country economic scale into consideration, which may cause some bias for estimations of international trade competitiveness.…”
Section: Measurement Of the International Competitiveness Trendmentioning
confidence: 99%